2011
DOI: 10.1007/s00270-011-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Temporary Occlusion of the Internal Iliac Arteries as Prophylaxis in Cesarean Section at Risk of Hemorrhage in Placenta Accreta

Abstract: The results demonstrated that prophylactic balloon occlusion of internal iliac artery is a safe method and appears to reduce blood loss and transfusion requirements in patients diagnosed with placenta accreta who undergo cesarean hysterectomy. Antenatal imaging diagnosis of placenta accreta enables preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
109
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 20 publications
1
109
0
5
Order By: Relevance
“…Previous case series that have been published indicate that the combined procedure is preferable, because it means treatment is more likely to be effective 3 . Our experience has borne out prior reports 4 suggesting that prophylactic occlusion of the internal iliac arteries can alone be effective for controlling massive blood loss, while offering the advantages of reduced radiation exposure and a lower risk of ischemia of the uterus or other pelvic organs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous case series that have been published indicate that the combined procedure is preferable, because it means treatment is more likely to be effective 3 . Our experience has borne out prior reports 4 suggesting that prophylactic occlusion of the internal iliac arteries can alone be effective for controlling massive blood loss, while offering the advantages of reduced radiation exposure and a lower risk of ischemia of the uterus or other pelvic organs.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the technique offers the benefit of reduced overall maternal morbidity and may also reduce costs 4,6,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaginal ischemia 7 and thromboembolism of the iliac, femoral, and popliteal arteries has been described. [7][8][9][10][11] Vascular rupture is less commonly described as a complication. Bishop described a case of a leaking pseudoaneurysm that was discovered after abdominal closure.…”
Section: Discussionmentioning
confidence: 99%
“…However the substantial network of collateral vessels in the female pelvis, many times limit the efficacy of this technique [13][14][15][16][17].…”
mentioning
confidence: 99%